Private Investment and Economic Growth in Cameroon - Nina, Yaoudey Dabal (Future Science / FSH-PH Publications, 2021)
The public authorities, in agreement with the private sector, are looking for the optimal solution that would enable the national economy to be more competitive in order to emerge by 2035. Indeed, one of the solutions lies in the country's ability to make private investment the growth factor. It is with this in mind that the purpose of this work is to analyze the effects of private investment on economic growth in Cameroon according to the nature of the transmission channel. To achieve this, we presented the concepts of the study as well as the literature on the relationship between them. Then we proceeded to empirical verification of the relationship between private investment and economic growth. A multiple linear regression model allowed us to relate these two concepts. Using the ordinary least squares (OLS) method in time series over the period 1990-2016, it appears that private investment has a positive influence on economic growth in Cameroon through the direct and indirect transmission channel.